2023
DOI: 10.1161/atvbaha.122.318149
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Ascending Thoracic Aortic Diameter and Blood Pressure: A Mendelian Randomization Study

Abstract: Background: Observational studies identified elevated blood pressure (BP) as a strong risk factor for thoracic aortic dilation, and BP reduction is the primary medical intervention recommended to prevent progression of aortic aneurysms. However, although BP may impact aortic dilation, aortic size may also impact BP. The causal relationship between BP and thoracic aortic size has not been reliably established. Methods: Genome-wide association studies sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Although males showed significantly larger mid-AAoD than females, no causal relationship between sex and mid-AAoD was found, suggesting that the difference is likely confounded by height and BSA. As shown in other studies 35,13,36 , we observed a larger mid-AAoD in hypertensive subjects independent of age and BSA. Causal analysis confirmed direct causal relations between hypertension and mid-AAoD.…”
Section: ) Statistical and Causal Analysis: Determinants Of Ascending...supporting
confidence: 90%
See 2 more Smart Citations
“…Although males showed significantly larger mid-AAoD than females, no causal relationship between sex and mid-AAoD was found, suggesting that the difference is likely confounded by height and BSA. As shown in other studies 35,13,36 , we observed a larger mid-AAoD in hypertensive subjects independent of age and BSA. Causal analysis confirmed direct causal relations between hypertension and mid-AAoD.…”
Section: ) Statistical and Causal Analysis: Determinants Of Ascending...supporting
confidence: 90%
“…Previous studies performed automated analysis of the thoracic aorta either on CT data 25,26,11,27 or only analyzed single points instead of describing the whole thoracic aorta 14,15,13 . To overcome these limitations, we improved our previous DL-based framework 20 for three-dimensional segmentation of the thoracic aorta in NE-MRA by simultaneously predicting landmark points on the thoracic aorta.…”
Section: ) Shape Analysis Of the Thoracic Aortamentioning
confidence: 99%
See 1 more Smart Citation
“…In a mendelian randomization analysis from the UK Biobank and MVP, genetically predicted SBP, DBP, and mean arterial pressure were all associated with increased ascending thoracic aortic diameter (all P <0.05). 102…”
Section: Peripheral Artery Disease and Aortic Diseasesmentioning
confidence: 99%